PENGARUH PELATIHAN KERJA, PENGAWASAN, DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA KARYAWANPADA PTPN X PG. NGADIREJO KEDIRI - Septia Jazaanil Husna; Endah Kurniawati; Ririn Wahyu Arida (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to determine and explain the effect of Job Training, Supervision, and Extrinsic Motivation on Employee Performance at PTPN X PG. Ngadirejo Kediri. Researchers took information by conducting interviews, observations and distributing questionnaires to company employees. The type of research used is quantitative with a sampling technique using random sampling with the slovin method as many as 111 respondents. The analysis technique used using the SPSS version 26 program includes Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Regression Test, t-test (Partial), F-test (Simultaneous), Coefficient of Determination Test (R2). Based on the results of the regression equation research, namely Y = 1.685 + 0.407X1 + 0.306X2 + 0.289X3. as a whole it can be concluded that the results of the t-test variable Job Training (X1) have a partially significant effect on Employee Performance (Y) with a Sig. 0.000 <0.05, the variable of Supervision (X2) has a partially significant effect on Employee Performance (Y) with a value of Sig. 0.003 <0.05 and the variable Extrinsic Motivation (X3) has a partially significant effect on Employee Performance (Y) with a Sig. 0.047 <0.05. Sig. Value F of 0.000 <0.05 indicates that the variables Job Training (X1), Supervision (X2) and Extrinsic Motivation (X3) have a significant effect simultaneously on Employee Performance at PTPN X PG. Ngadirejo Kediri. =